Real-time reverse transcription polymerase chain reaction techniques: usefulness as an animal viral disease diagnostic - Manojkumar, Ramanunninair (Slovenian veterinary research, 2006)
Quick and early diagnosis of the causative agents is critical for countries which are enzootic to particular disease. In these diagnostics speed is paramount; Real-time Reverse Transcription PCR (rRT-PCR) is being utilized increasingly in novel clinical diagnostic assays in molecular biology. The combination of excellent sensitivity and specificity made this technique an alternative to cell culture and other laboratory testing methods for disease diagnosis. In this review, the usefulness or applications of rRT-PCR assays inthe diagnosis of some of the important animal viral infections are summarized.
Keywords: Diagnosis; Polimerazna, verižna reakcija; Polymerase Chain Reaction; Retroviridae Infections; Retroviridne infekcije; Rna Viruses; RNA virusi; Virus Diseases; Virusne bolezni